Nurses’ Knowledge Toward Lower Back Pain: A Cross-Sectional Study: Pengetahuan Perawat Terhadap Nyeri Punggung Bawah: Sebuah Studi Cross-Sectional - Mahfoudh Falih Hasan; Wathiq Faraon Hussein; Ali Malik Tiryag; Imama J Ali; Zainab M Shaker (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Nursing is one of the occupations with the highest risk of developing musculoskeletal issues. Objectives: To assess the level of nurses' knowledge toward lower back pain. Methods: This study was carried out on the nursing staff in different hospitals and comprised a sample of sixty nurses, twenty-six of whom were male and thirty-four of whom were female. The questionnaire was used to gather the necessary data. It consists of 24 questions about lower back pain and its exercises in various situations, with an overall score of 48 (I strongly agree = 2, I agree = 1, I don't agree = 0) and variables (education level and years of experience). And examine the outcomes using the statistical software (spss). The data was analyzed in version 26 of the Statistical Package for Social Sciences (SPSS). Results: Nursing Staff's knowledge via ANOVA test. Poor level mean was (13.00), and Sd was (3.46). Medium level mean was (25.06), Sd was (3.43). Good level mean was (36.14), Sd (7.20). Conclusion: Most of the nurses are pass regarding exercise domain of lower back pain. Demographic factors and nurses' physiotherapy knowledge do not significantly correlate. Highlight: Nurses face high risk of musculoskeletal issues, including lower back pain. Surveyed 60 nurses using 24-questionnaire; analyzed with SPSS version 26. Most nurses passed; no significant correlation with demographic factors. Keywords: Nurses, Knowledge, Lower Back Pain